2022
DOI: 10.1002/chem.202201407
|View full text |Cite
|
Sign up to set email alerts
|

Prussian Blue Type Cocatalysts for Enhancing the Photocatalytic Water Oxidation Performance of BiVO4

Abstract: The efficiency of photocatalytic overall water splitting reactions is usually limited by the high energy barrier and complex multiple electron‐transfer processes of the oxygen evolution reaction (OER). Although bismuth vanadate (BiVO4) as the photocatalyst has been developed for enhancing the kinetics of the water oxidation reaction, it still suffers from challenges of fast recombination of photogenerated electron‐hole pairs and poor photocatalytic activity. Herein, six MII‐CoIII Prussian blue analogues (PBAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In addition, metal phthalocyanine such as CuPc, CoPc-(NH 2 ) 4 and M II -Co III prussian blue analogues (M=Mn, Fe, Co, Ni, Cu and ZnO) cocatalysts were synthesized and deposited on the surface of BiVO 4 for boosting the surface catalytic efficiency and enhancing photoinduced carries separation efficiency of BiVO 4 . [54,55] For example, the CuPc ultrathin layer was introduced at the interface of BiVO 4 and NiCo-LDH layer as a hole transport highway to promote the extraction and transport of photoinduced holes, which improved the PEC water splitting performance of the BiVO 4 photoanode due to inhibiting the charge recombination, [56] as shown in Figure 11(a-d activity (Figure 11f). They found that photoinduced hole accumulation was present in the CuFe PB layer, which resulted in higher charge extraction from the BiVO 4 surface.…”
Section: Molecular Metal Complexesmentioning
confidence: 99%
“…In addition, metal phthalocyanine such as CuPc, CoPc-(NH 2 ) 4 and M II -Co III prussian blue analogues (M=Mn, Fe, Co, Ni, Cu and ZnO) cocatalysts were synthesized and deposited on the surface of BiVO 4 for boosting the surface catalytic efficiency and enhancing photoinduced carries separation efficiency of BiVO 4 . [54,55] For example, the CuPc ultrathin layer was introduced at the interface of BiVO 4 and NiCo-LDH layer as a hole transport highway to promote the extraction and transport of photoinduced holes, which improved the PEC water splitting performance of the BiVO 4 photoanode due to inhibiting the charge recombination, [56] as shown in Figure 11(a-d activity (Figure 11f). They found that photoinduced hole accumulation was present in the CuFe PB layer, which resulted in higher charge extraction from the BiVO 4 surface.…”
Section: Molecular Metal Complexesmentioning
confidence: 99%
“…Prussian blue (PB) is the oldest and simplest metal organic frameworks (MOF) material, which is favored by researchers due to its good durability and cycle stability, suitable redox reaction area, and simple preparation process. , However, compared with traditional semiconductor photocatalysts, pure PB has lower photocatalytic activity due to its poor electron conductivity. It has been proved that the combination of PB and other semiconductor materials is one of the ideal strategies to improve its photocatalytic activity. For instance, Mao et al prepared the TiO 2 @PB composite film using a hydrothermal and electrodeposition method . The TiO 2 @PB photoanode showed a high photocatalytic activity and photocurrent density due to the formation of the TiO 2 /PB heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…1,[19][20][21][22][23] For example, Prussian blue analogs (PBAs), a sub-class of MOF, have been demonstrated as cocatalysts for photocatalytic and photoelectrochemical water oxidation. [24][25][26][27][28][29] PBAs are well explored as electrocatalysts for water splitting and efficient materials for metal-ion batteries. 16,[30][31][32][33] Only recently, Ferdi's and Mascarós' groups have demonstrated the use of PBAs as cocatalysts that can modulate the energy levels of a photocatalyst.…”
Section: Introductionmentioning
confidence: 99%